Предмет: Математика, автор: VovantozZz

Решить первое задание.

Приложения:

Ответы

Автор ответа: Newtion
0
displaystyle cos (pi-alpha)=cos pi cos alpha +sin pi sin alpha=-cos alpha\\cosleft( frac{pi}{2}-alpha right)=sin alpha\\sin (2pi -alpha)=sin (-alpha+2pi)=sin (-alpha)=-sin alpha\\sin left( frac{3pi}{2}-alpha right)=sin  frac{3pi}{2}cos alpha-cos  frac{3pi}{2}sin alpha=-cos alpha

Т.е. 

displaystylefrac{-cos alpha+sin alpha}{-sin alpha+cos alpha} = frac{-cos alpha+sin alpha}{-(-cos alpha+sin alpha)} =-1
Похожие вопросы